Pengaruh Jarak Antar Ulir Terhadap Daya Output Pada Turbin Archimedes Screw - Jasron, Jahirwan Ut; A. Silla, Wilson Mardianto; Gusnawati, Gusnawati (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
The need for energy sources currently continues to increase, especially electrical energy, even exceeding existing estimates. Along with the need for electrical energy, further research is needed to utilize new renewable energy as alternative energy, one of which is hydroelectric power plants. Hydropower and PLTMH have different output capacities, one of the turbines that can be used as a PLTMH is the screw turbine (Archimedes screw). The efficiency of the Archimedes screw turbine is influenced by many factors, one of which is the turbine design. The existing turbine design needs to be evaluated by several factors such as inner and outer screw diameter, slope, screw pitch, number of blades, and inlet and outlet conditions as well as head and water flow. This research aims to find out how the design of the distance between the screws affects the efficiency of this screw turbine. The variable used in this research is the distance between threads, namely 8 cm, 10 cm, and 12 cm with a 12VDC 5W, 10W, and 15W lamp load. The results of this research show that the turbine with a distance between the threads of 12 cm produces the highest generator rotation, namely 532.1 rpm at no load and at a load of 15 watts the rotation decreases to 227.1 rpm. The highest voltage produced is 27.1 Volts when there is no load and when the load is 15 watts it is 8.9 Volts. while the current and power are 0.64 Ampere 5.70 Watt respectively, so that the highest efficiency is produced in a turbine with a screw spacing of 12 cm at a turbine head angle of 40 , namely 10.10%.